Development of database and mathematical models for predicting engine performance parameters using biodiesel - Pranav, P. K.; Patel, Thaneswer; Singh, K. Padmeshore (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: A database for complete and quick knowledge of biodiesel was developed in Microsoft access linked with interactive interfaced of Visual Basic which contains various information such as biodiesel properties, engine performance parameters and emission characteristics. The comparisons of fuel properties among the biodiesel, its blends and engine performance parameters are one of the most attractive features of the developed database. Based on the data collected from the developed database, the analysis of variance (ANOVA) was carried out to know the effect of fuel properties on engine performance parameters. The fuel properties such as a change in calorific value and viscosity with respect to diesel were found to be significant at 5% level with brake power (BP) and brake specific fuel consumption (BSFC). However, flash point and density were found to be insignificant. Therefore, mathematical models were developed for (i) change in BP and (ii) BSFC based on the significant fuel properties. The model efficiency for BP and BSFC were found to be 92% and 91% respectively. The RMSE values were also calculated from the predicted value and found to be 1.85 and 5.45 for BP and BSFC respectively. From the above statistical facts, it is revealed that the developed mathematical models can be used to predict the change in BP and BSFC. Further, it is also expected that the developed database shall be expedient for researchers and engineers to locate various information related to biodiesel.Keywords: biodiesel, engine performance, database, mathematical models, brake power, BSFCDOI: 10.3965/j.ijabe.20171003.1789Citation: Pranav P K, Patel T, Singh K P. Development of database and mathematical models for predicting engine performance parameters using biodiesel. Int J Agric & Biol Eng, 2017; 10(3): 121–129.